A Deletion Mutation Placing the Galactokinase Gene of Escherichia coli under Control of the Biotin Promoter - Ketner, Gary (1974)
A deletion has been isolated which fuses galK and presumably galT to the promoter and operator of the bioA operon. The deletion has endpoints in bioA and galE, and leaves the operator-proximal end of bioA intact and the regulatory sites themselves functional. In bacterial strains which carry the deletion, the expression of galK is regulated by biotin, although due to the inefficiency of the bioA promoter even the fully derepressed level of galactokinase is low. Electron micrographic examination of the mutation shows that it is a simple deletion, uncomplicated by other chromosomal abnormalities.